HIPOTÉTICA ETAPA PREBIÓTICA - Villegas V., Bayardo; Departamento de Matemáticas Facultad de Ciencias Pontificia Universidad Javeriana (2013)
It is commonly believed that life began in the prebiotic epoch with ribozymes: as a solution to the objection that the harsh enviroamental conditions during the aforesaid epoch would impede the autoreplication of the ribozymes, the hypothesis is proposed, based on the resistance of prions to this type of conditions, that "at sorne point in prebiotic time a ribozyme/prion association, type +1+, occurred". In arder to support this hypothésis arguments and bibliographic information are presented